Price Level Convergence in Turkey - Çakır, Mustafa; Gündüz, Lokman (Taylor & Francis Group, 2021)
This paper examines price convergence among 26 regions of Turkey using general and disaggregated monthly consumer prices between 2005 and 2019. In contrast to previous studies, the results provide evidence for convergence clubs (multiple equilibria) and support the heterogeneity of consumer prices across Turkish regions. This finding is particularly valid for the disaggregated prices where there exist two to four clubs. There is also an increase in the number of convergence clubs in recent years. That is, market integration or the law of one price in Turkey does not appear to be achieved not only for the prices of nontradable goods but also for those of tradable goods either, most likely due to a combination of factors including higher exchange rate volatility, rising inflation and unrelenting regional socio-economic disparities. Our results show that the inflation-targeting regime does not help converge the consumer price levels across the regions.
Keywords: Club Convergence; Convergence; Consumer Prices; Log t Test; Turkey